Scientific-organizational activity of Russian technical society in 1866-1917 - Pylypchuk, O. O. (History of science and technology, 2013)
The article notes that scientific interest to one of the fundamental problems of national history – the phenomenon of science in public organizations – recently increases. Scientific societies are an old form of association of scientists, in which the science found its organizational expression. The establishment and development of national scientific and technical societies, the formation of their organizational structure and research staff are inseparably linked with the history of our Motherland. Dui to its exceptional position in a country as a scientific collective which received support of state power, Russian technical society was stipulated in its scientific-organizational activity, preservation of spiritual values and development of cultural heritage, in particular in the scientific and technical sphere.